A realistic quasi-physical model of the 100 metre dash - Mureika, J. R. (Canadian Journal of Physics, 2001)
A quasi-physical model (having both physical and mathematical roots) of sprint performances is presented, accounting for the influence of drag modification via wind and altitude variations. The race time corrections for both men and women sprinters are discussed, and theoretical estimates for the associated drag areas are presented. The corrections are consistent with constant-wind estimates of previous authors, however those for variable wind are more accentuated for this model. As a practical example, the nullified World Record and 1988 Olympic 100 m race of Ben Johnson is studied, and compared with the present World Record of 9.79 s.